Trajectory following with a MAV under Rotor Fault Conditions - Pose, Claudio Daniel (2020)
Lately, a novel multirotor aerial vehicle capable of handling single rotor failures was presented. When a rotor fails, physically reconfiguring one of the remaining rotors of a hexarotor allows to compensate for maneuverability limitations. In this work, experimental results show the performance of the vehicle in a trajectory-following task in both nominal and fault conditions.